2023
DOI: 10.21037/qims-22-551
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning-based image analysis of eyelid morphology in thyroid-associated ophthalmopathy

Abstract: Background:We aimed to propose a deep learning-based approach to automatically measure eyelid morphology in patients with thyroid-associated ophthalmopathy (TAO).Methods: This prospective study consecutively included 74 eyes of patients with TAO and 74 eyes of healthy volunteers visiting the ophthalmology department in a tertiary A hospital. Patients diagnosed as TAO and healthy volunteers who were age-and gender-matched met the eligibility criteria for recruitment.Facial images were taken under the same light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The most common AI models used in these studies are convolutional neural networks (CNN). Three of the studies validated algorithms on external datasets ( 18 , 23 , 26 ). 12 of the 13 studies compared algorithm performance against healthcare professionals, whereas one study utilizes electronic medical records (EMR) phenotypes ( 15 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common AI models used in these studies are convolutional neural networks (CNN). Three of the studies validated algorithms on external datasets ( 18 , 23 , 26 ). 12 of the 13 studies compared algorithm performance against healthcare professionals, whereas one study utilizes electronic medical records (EMR) phenotypes ( 15 ).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies utilized facial photos to detect signs of TED ( 21 , 23 , 26 ) or assess disease activity ( 27 ). Outcomes assessed were heterogenous amongst studies: diagnosis of TED ( 23 ) presence of severe signs of TED ( 21 ), eyelid morphology in TED ( 26 ) and prediction of CAS score ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Doppler imaging of orbital vessels were also used to evaluate the activity and severity of TAO 17 . In addition, another study proposed a DL-based system that allowed automatic, comprehensive, and objective measurement of eyelid morphology in TAO by using facial images, which might have some potential application prospects in the management of TAO 18 . However, the limitations of these studies include the complex clinical examinations and the relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Lou et al reported an image analysis technique using a deep learning method to compare surgical outcomes before and after blepharoplasty based on facial digital photographs taken separately [17].…”
Section: Discussionmentioning
confidence: 99%